Abiotic and biotic degradation of trace pharmaceuticals in anaerobic digesters supplemented with powdered activated carbon (PAC) (EN-60AB) - Yap, Xiu En (2016)
This report is about experiments on adsorption and biodegradation of pharmaceutically active compounds (PhACs) on powdered activated carbon (PAC) and anaerobic digestion sludge. The adsorption isotherm of the selected PhACs on PAC was determined first. The PhACs used in this experiment were Carbamazepine (CBZ), Sulfamethoxazole (SMX), Trimethoprim (TMP), Diclofenac Sodium (DCF-Na), Triclosan (TCS). After the testing, all the outcomes showed similar increasing trend on the PAC adsorption. The abiotic and biotic degradation of PhACs on PAC and anaerobic digestion sludge, and the impact of sludge on PAC adsorption were then investigated. Three different conditions were tested out to determine the rate of degradation and impact of sludge on PAC adsorption. From the outcomes of the experiment, it proves that sludge would not affect the PAC adsorption and adsorption and degradation could happen at the same. When both sludge and PAC was present, it was found out that the sludge and PAC would compete between themselves for adsorption. Lastly, the result from the trial shows that degradation needs time to occur.